Tendências e contradições do processo de expansão do segmento mercantil-capitalista de provisão de moradias na região de Venda Nova- Belo Horizonte/MG - Lucia Karine de Almeida (2009)
The process of land occupation in Belo Horizonte is marked by the support of the State as well as the real estate market as main agents in the production of the urban space. The analysis of Venda Nova region and adjoining areas shows the recent expansion on the performance of the mercantile segment of the housing production in peripheral areas of the metropolis. This expansion resulted from the increase of the properties value through urban improvements and the urban populations increasing of income, among others, and is characterized by innovations in the concept of housing for the middle class. Economically profitable to the real estate market such action can change the urban dynamic of the city and aggravate historical socio-spatial differences. The performance of the mercantile capitalist segment of housing production is differentiated in this work by the form of performance in two types: state or enterprise action. The focus of the research is the enterprise production, that have, for its turn, two submarkets: competitive and monopolist. As in the analyzed period, from 1997 to 2007, there was no evidence of housings production by the monopolist submarket in the study area, the work details the main aspects related to the enterprise production of the competitive submarket: demands, types of agents, market strategies, real estate products offered and homogeneous characteristics of occupation. The apartments and semidetacheds houses are the two real estate products more offered by this submarket and therefore they are analyzed under the conceptual, sociocultural, architectural and marketing aspects.All the analyses are based on theoretical concepts, historical data and in apprehended empirical research throughout the work elaboration. The objective is contextualized and shows the trends, contradictions and possible impacts in the urban dynamics of the process of mercantile expansion of provision of housings in the study area